2018
DOI: 10.1097/md.0000000000010068
|View full text |Cite
|
Sign up to set email alerts
|

Aggravation and subsequent disappearance of cervical disc herniation after cervical open-door laminoplasty

Abstract: Rationale:Cervical open-door laminoplasty can enlarge the volume of the cervical vertebral canal and thus has become an effective and safe treatment for multilevel cervical disc herniation and cervical stenosis. Some post-surgery complications exist, such as reduction of cervical alignment and local kyphosis. However, aggravation of cervical disc herniation at the surgical level during short-term follow-up has not been discussed. Additionally, spontaneous disappearance of herniated disc pulposus is a common ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Operation of EOLP was herein used as the surgicalcontrol, as the classic operation widely used over a halfcentury after invention. 18 EOLP was previously shown to able to cause CDH regression, documented by several case reports 19,20 and retrospective study. 21 Case reports 19,20 presented a single case that was unique but showing great diminishment of CDH after EOLP, which was also seen in this study (3.7% of CDH regress <À50%).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Operation of EOLP was herein used as the surgicalcontrol, as the classic operation widely used over a halfcentury after invention. 18 EOLP was previously shown to able to cause CDH regression, documented by several case reports 19,20 and retrospective study. 21 Case reports 19,20 presented a single case that was unique but showing great diminishment of CDH after EOLP, which was also seen in this study (3.7% of CDH regress <À50%).…”
Section: Discussionmentioning
confidence: 95%
“…18 EOLP was previously shown to able to cause CDH regression, documented by several case reports 19,20 and retrospective study. 21 Case reports 19,20 presented a single case that was unique but showing great diminishment of CDH after EOLP, which was also seen in this study (3.7% of CDH regress <À50%). The percentage changes of CDH size has been shown as À9.59% in mean from EOLP patients, 21 which was also close to our data (À5.4% in median).…”
Section: Discussionmentioning
confidence: 95%
“…Degenerative cervical anatomic change is the most frequently seen of CCS and can result from osteophyte formation, bulged disc, and cervical facet hypertrophy. [ 14 , 15 ] Previous research has found that the relationships between the cervical dura- sac thickness, narrowed spinal canal, and cervical lateral masses are closely associated with disc aging, degeneration, and CCS. [ 16 ] Kayalioglu et al have reported that the pedicles of cervical vertebrae are strong structural anatomic elements of the cervical vertebrae and offer the strength of attachment to the cervical spine.…”
Section: Discussionmentioning
confidence: 99%